2021
DOI: 10.1113/ep088937
|View full text |Cite
|
Sign up to set email alerts
|

Platelet releasate normalises the compromised muscle regeneration in a mouse model of hyperlipidaemia

Abstract: New Findings What is the central question of this study?What is the impact of obesity‐independent hyperlipidaemia on skeletal muscle stem cell function of ApoE‐deficient (ApoE–/–) mice? What is the main finding and its importance?Compromised muscle stem cell function accounts for the impaired muscle regeneration in hyperlipidaemic ApoE–/– mice. Importantly, impaired muscle regeneration is normalised by administration of platelet releasate. Abstract Muscle satellite cells are important stem cells for skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Interestingly, several studies have explored the therapeutic use of the platelet-rich plasma (PRP), i.e., the component of the blood devoid of white and red blood cells but rich in platelets and platelet-secreted factors (releasate). In particular, injection of the PRP has been proposed to boost wound healing and regeneration in a number of tissues [50][51][52][53][54][55][56][57][58] , including skeletal muscle [59][60][61][62][63][64] . However, it remains largely undetermined whether platelets are necessary for skeletal muscle regeneration beyond their role in hemostasis, and whether platelet-secreted factors are required for any step of muscle repair.…”
mentioning
confidence: 99%
“…Interestingly, several studies have explored the therapeutic use of the platelet-rich plasma (PRP), i.e., the component of the blood devoid of white and red blood cells but rich in platelets and platelet-secreted factors (releasate). In particular, injection of the PRP has been proposed to boost wound healing and regeneration in a number of tissues [50][51][52][53][54][55][56][57][58] , including skeletal muscle [59][60][61][62][63][64] . However, it remains largely undetermined whether platelets are necessary for skeletal muscle regeneration beyond their role in hemostasis, and whether platelet-secreted factors are required for any step of muscle repair.…”
mentioning
confidence: 99%
“…2g, h ). Surprisingly, the remaining Pax7 + cell population (Pax7_PGs-3) demonstrated expression of genes indicative of satellite cells in vivo, including Apold1 53 , Apoe 53 , 54 , CD9 55 , Cebpb 56 and most notably absence of Cdkn1c , a myoblast marker reportedly undetectable in muscle stem cells 57 (Figs. 2g–i and S6a–c ).…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31]33] In agreement with this possibility, an interesting study found that intraperitoneal injection of the PR from wild-type platelets can rescue the muscle regeneration deficits of ApoE knockout mice, at least in part by promoting myoD and myogenin expression in differentiating myoblasts, and by promoting the growth of newly formed myofibers. [35] The decreased regenerative capacity of ApoE knockout mice arises from hyperlipidemia and metabolic stress, suggesting that the systemic delivery of the PR from wild-type mice may help normalize metabolism in ApoE knockout mice, possibly via ApoE released by platelets. [2,3] Further studies should determine whether platelets and the PR influence myogenesis in distinct disease contexts and whether this response also occurs in vivo in physiological conditions (i.e., in wild-type mice).…”
Section: Platelet-secreted Factors Can Promote Myoblast Proliferation...mentioning
confidence: 99%